Throw Down Your Heart: Tales From the Acoustic Planet Vol. 3, the Africa Sessions, 2009, Bela Fleck, produced by Bela Fleck. Rounder/Umgd CDROUN0634. One compact disc. 32-page booklet with liner notes by Fleck and photography by Dave Sinko, Joel Hamburger, Dave Bergen, Sascha Paladino and Nicole Smaglick. - Krakauer, Ben (International Library of African Music, 2009)
pages: 176-177
Keywords: African Music